Malaysia : Publication of Financial Sector Assessment Program Documentation-Detailed Assessment of Implementation of IOSCO Objectives and Principles of Securities Regulation. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
The article is an account of the assessment of implementation of IOSCO principles of securities and regulations in Malaysia. This assessment was conducted by the International Monetary fund (IMF) and the World Bank. The Securities Commission Malaysia has developed its supervisory network. The rules of the governing bodies such as issuers, auditors, collective investment schemes, and markets have widened their roles. The Executive Board conducted the assessment to ascertain whether the legal securities are able to meet the standards set by the IOSCO.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet